Effectiveness of Animal Assisted Therapy on Social Interaction: A Meta-Analysis - Fifi Alviana; Yueh-Juen Hwu; Jiun-Iung Lei (GLOBAL HEALTH SCIENCE GROUP, 2020)
Animal-assisted therapy (AAT) is one of the non-pharmacological and complementary interventions. AAT has been practiced for many years and now a lot of progress are being made. However, the effect of AAT on social interaction is not well understood. The purpose of this meta-analysis was to present the best available evidence regarding the effects of AAT on social interaction including blood pressure, cognitive function, and communication. Researchers searched seven electronic databases for relevant articles published between 1984 and 2014. Data were collected using inclusion and exclusion criteria. The Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument was used to evaluate the quality of the identified articles.Six RCTs and three pseudorandomized controlled trial published within 1995-2011 with 281 participants had extractable data. The result of the meta-analysis indicated that AAT had an effect on increasing communication. The results were not statistically for blood pressure and cognitive function. There are a number of promising indications, in view of the limited number and quality of studies and the variation in results among studies. This review highlights the need for additional well-designed trials to draw conclusions that are more robust.